The Influence of Principal Leadership and Work Motivation on Teacher Performance - Ulfathmi, Ulfathmi; Arafat, Yasir; Setiawan, Andi Arif (Journal of Social Work and Science Education, 2021)
The leadership of the principal is a determining factor for the success of the quality of educators. Good leadership will also create a good work environment, so that high teacher work motivation will emerge. Teacher work motivation is a drive from within and encouragement from outside to carry out work, so that teacher work motivation can be one of the factors that can affect the ups and downs of teacher performance. The purpose of this study was to determine the effect of principal leadership, teacher motivation on teacher performance at SMP 32 OKU. The method used in this research is quantitative with ex post facto type. The population in this study were 58 teachers of SMP 32 OKU. The data collection techniques used were questionnaires and documentation. The data analysis technique used is the analysis prerequisite test, including the normality test, autocorrelation test, heteroscedasticity test and multicollinearity test, and heteroscedasticity. The final analysis test uses the one-sample t-test, simple and multiple correlation analysis, simple and multiple regression analysis, the coefficient of determination, and the f-test.